Flaner ekologiczny Filipa Springera jako odpowiedź literatury non-fiction na katastrofę klimatyczną - Kamiński, Szymon (Zagadnienia Rodzajów Literackich, 2023)
The greatest popularity of the phenomenon of flânerie appears in the periodof modernism, when it was often used by poets and writers to describe the expression and dynamics of an individual. Flaneur, the carefree hero aimlessly strolling around the city, described everyday life, filtering it through his own perception. However, can the flaneur figure still be used today, and have any innovative potential? Reporter Filip Springer seems to be one of the authors whose texts play with the modernist dimension of the flaneur. As a result of shifting the Focus from the aesthetic to the ethical, a new strategy of action is revealed, which I call the ecological flaneur, an environmental walk during which one experiences a reality changed by human activity and as a result of climate change caused by it. Based on the series Zmiana klimatu już tu jest and Wyprawa po nadzieję, as well as a collection of reports Wanna z kolumnadą. Reportaże o polskiej przestrzeni, I will trace the changes made by the reporter in the modernist dimension of the flaneur.